Penerimaan Diri dan Kepuasan Pernikahan pada Orang Tua dari Anak Penyandang Autisme - Joanagytha, Mia; Pandia, Weny Savitry S. (MANASA, 2025)
Parents of children with autism often experience lower levels of marital satisfaction. Achieving marital satisfaction is challenging, as it develops over a long period of time. Many studies indicate that self-acceptance is among the key factors associated with marital satisfaction. However, further research is needed to better understand the relationship between these two variables, particularly given the unique challenges faced by families raising children with autism. This study aims to examine the relationship between self-acceptance and marital satisfaction among parents of children with autism. A quantitative approach with correlational explanatory design was employed. Data was collected using convenience sampling, involving 24 married couples who have children with autism. The results showed no significant relationship between self-acceptance and marital satisfaction of parents of children with autism. Further research is recommended to explore additional variables that may mediate the relationship between self-acceptance and marital satisfaction.